The Image of Children in Charles Dickens and Abdulla Kahhor's Works (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The image of children in the works of Charles Dickens and Abdulla Kahhor reflects the social and cultural contexts of their respective time periods. Both authors present children as vulnerable and innocent beings who are often mistreated and marginalized by society. However, while Dickens portrays children as victims of poverty and exploitation in Victorian England, Kahhor's depiction of children in the context highlights the impact of political instability and economic hardships on their lives. This paper explores how both authors use the image of children to shed light on larger social issues and to evoke empathy and compassion from their readers.